PENGARUH KUALITAS LAYANAN DAN MEMORABLE TOURISM EXPERIENCE TERHADAP KEPUASAN SERTA LOYALITAS WISATAWAN PADA KONDISI MENUJU NEW NORMAL - Eny Endah Pujiastuti (Business UHO: Jurnal Administrasi Bisnis, 2022)
Currently, the government and destination managers are trying to recover from the crisis caused by the covid 19 pandemic. One of the ways to do this is through communication or promotion through digital marketing in order to generate and increase tourist demand. Therefore, the formulation of the problem as well as the purpose of this study is to analyze and prove: (1) the significant influence of service quality on tourist satisfaction. (2) significant influence of memorable tourism experience on tourist satisfaction, (3) significant influence of service quality on tourist loyalty, (4) significant influence of memorable tourism experience on tourist loyalty. (5) significant influence of tourist satisfaction on tourist loyalty, (6). Significant effect of service quality on tourist loyalty through Tourist Satisfaction. (7). Significant influence of memorable tourism experience on tourist loyalty through Tourist Satisfaction. The research was conducted in the tourist destination of Sarangan Lake, Magetan, East Java. The sample criteria used are tourists who have visited at least 2 times (twice). Data collection using google form. In this study, 129 effective questionnaires were collected which will then be processed using Structural Equating Modeling (SEM) which is operated using the AMOS application. This study concludes that (1) service quality has a significant effect on tourist satisfaction. (2) memorable tourism experience has a significant effect on tourist satisfaction, (3) service quality has a significant influence on tourist loyalty, (4) memorable tourism experience has a significant influence on tourist loyalty. (5) tourist satisfaction has a significant effect on tourist loyalty, (6). service quality has a significant effect on tourist loyalty through tourist satisfaction. (7). memorable tourism experience has a significant influence on tourist loyalty through tourist satisfaction